If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1k + 35 = -7(-5 + -8k) Reorder the terms: 35 + -1k = -7(-5 + -8k) 35 + -1k = (-5 * -7 + -8k * -7) 35 + -1k = (35 + 56k) Add '-35' to each side of the equation. 35 + -35 + -1k = 35 + -35 + 56k Combine like terms: 35 + -35 = 0 0 + -1k = 35 + -35 + 56k -1k = 35 + -35 + 56k Combine like terms: 35 + -35 = 0 -1k = 0 + 56k -1k = 56k Solving -1k = 56k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-56k' to each side of the equation. -1k + -56k = 56k + -56k Combine like terms: -1k + -56k = -57k -57k = 56k + -56k Combine like terms: 56k + -56k = 0 -57k = 0 Divide each side by '-57'. k = 0 Simplifying k = 0
| 107+2x-5=180 | | 2(2+3y)+3y=15 | | x+2x-5=107 | | 9x^2-70+49=0 | | 2x+-3y(6x-11)=-7 | | (6x^2)-30x=0 | | (6x^2)-30y=0 | | (6x+48)=(12x+24) | | 26.2=9t | | 3b-3-4b=2 | | 10=1+r+5 | | y=4+0.01x | | x^4-2x^2-6x+3=0 | | 3z+6=5z-4 | | 26+3n=-2(n+2)-n | | X^3+13=6x | | 23=2u-11 | | (8x-20)+(3x+15)=88 | | 36=5(w+3)-8w | | 3a+a=4*2 | | 2x+48=9x+13 | | y=10-0.01x | | 5x-2-3x=3x-3-8 | | 7b-15=5b-s | | 5a+3b-c= | | 289= | | 4x+5y=126 | | 7x-4y=18 | | 11*(6x+11)= | | -95=5z | | d+5=17-8+6 | | 2x^4+9x-18=0 |